Towards a European Union child basic income? Within and between country effects - Horacio Levy; Manos Matsaganis; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper explores the within and between country distributional implications of an illustrative Child Basic Income (CBI) operated at EU level. Using EUROMOD, we establish that a universal payment of 50 per month per child aged under 6 could take 800,000 children in this age group out of poverty. It could be financed by an EU flat tax of 0.2% on all household income, assuming that it would also be taxed nationally as income. Most member states and virtually all families with children aged under 6 would be net gainers. We simulate two versions of EU CBI, with the benefit rate of 50 per month adjusted or not for differences in purchasing power between member states. In general, fiscal flows between member states, and also poverty reduction, would be smaller under the adjusted version. The political feasibility of such a scheme might be questioned, especially within the net contributor countries. Nevertheless, for those seeking ways to strengthen solidarity across national boundaries, a scheme supporting the incomes of families with young children, wherever in the EU they might reside could be a demonstration of the EU's commitment to children, to the future (EC 2012a: 62).
Keywords: C81; H71; I38; 330; child basic income; European Union; microsimulation